Synthesis and Evaluation of [11C]7-Halogen-2-Phenyl Isoindolone Derivatives: Potential PET Radioligands for in vivo Imaging of 5-HT2C Receptors - Zeng, Fanxing; Nye, Jonathon A.; Voll, Ronald J.; Mun, Jiyoung; Goodman, Mark M. (Frontiers in Neuroscience, 2021)
The serotonin 5-HT2C receptor (5-HT2CR) is abundantly expressed throughout the central nervous system, and involved in a variety of neuroendocrine and neurobehavioral processes. The development of a selective radioligand that will enable in vivo imaging and quantification of 5-HT2CR densities represents a significant technological advancement in understanding both the normal function and pathophysiology of the 5-HT2CR. Four 7-halogen-2-phenyl isoindolones (7-F, Cl, Br, I) were synthesized and displayed high affinities for 5-HT2CR and high selectivity over 5-HT2A and 5-HT2B. [11C]7-Chloro-2-[4-methoxy-3-[2-(4-methylpiperidin-1-yl)ethoxy]phenyl]isoindolin-1-one (6) and [11C]7-iodo-2-[4-methoxy-3-[2-(4-methylpiperidin-1-yl)ethoxy]phenyl]isoindolin-1-one (9) were synthesized in high radiochemical yield of 37−44% (n = 10, decay corrected from end of [11C]CH3I synthesis) with high radiochemical purity via O-methylation with [11C]CH3I, respectively. MicroPET imaging studies in male rats with or without 5-HT2C antagonist SB-242084 showed that [11C]6 and [11C]9 display specific bindings to 5-HT2CR in the choroid plexus and hippocampus. In vivo microPET brain imaging studies in rhesus monkeys demonstrated that [11C]6 and [11C]9 exhibit excellent blood-brain barrier penetration. The contrast of bindings to the choroid plexus and hippocampus compared to the cerebellum peaked at 2.7 and 1.6, respectively for [11C]6, and 3.7 and 2.7, respectively for [11C]9, which were reduced by administration of a dose of SB-242084. Our results support the candidacy of [11C]6 and [11C]9 for further study as radioligands for in vivo quantitation of 5-HT2C sites by PET.